Between Islamic Law and State in Zakat Collection: Legitimacy of Mosque Management (Takmir) - Bisyri, Mohammad Hasan; Ahmad, Shofian; Mubarok; Khasanah, Uswatun (Hikmatuna : Journal for Integrative Islamic Studies, 2024)
Zakat has enormous economic, social, and worship values. It has encouraged several social institutions to try to collect zakat funds for Islamic development (da'wah), one of which is carried out by the mosque management (takmir). However, many of them lack legal legitimacy. This article aims to analyse the legality of takmir that do not have legality as zakat fund collectors, explore the reasons for the lack of mosque takmir that have legal legality as zakat collecting institutions, and analyse the legal implications. The research employed a qualitative method utilizing a normative juridical approach. The primary data sources are structured interviews with the mosque management committee (takmir). The findings showed that first, most of the mosque takmir that function as zakat fund collectors do not have legal authorization. Second, six factors contribute to the lack of legal status: the difficulty in meeting the requirements for establishment as a LAZ, limited human resources, inadequate financial resources, community opposition to designating mosque takmir as UPZ, a lack of understanding among mosque takmirs regarding the process of establishing UPZ and Service Offices, and the presence of unofficial mosque takmir. Third: Implications of Zakat collection by mosque takmir who have no legality: Zakat is not distributed in its entirety to the mustahiq, and mosque takmir lacking legal status may face criminal liability. Additionally, the absence of legal recognition undermines legal certainty for both mosque takmir and muzakki.